Realitas Tersembunyi : Praktik Dramaturgi Mahasiswa Penerima Beasiswa KIPK - Anggun Putri Ady Triyas; Dwi Rizky Wulan Maulida; Elanda Cika Alodya Nathania (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The KIP-Kuliah Scholarship is study assistance for prospective students from limited economic backgrounds with academic achievements. Online registration makes the process easier, but opens up opportunities for fraud, especially in data manipulation. This research adopts Goffman's Dramaturgy theory, viewing social interactions as performances where scholarship applicants act like actors. As well as using the perspective of Risk Society theory by Ulrich Beck, which states that risk is present in modern society as the impact of changes in technology, economics and social structure. This research is qualitative research with a phenomenological approach. This research aims to reveal the front and back stages of students receiving KIPK scholarships. The results show dramaturgical practices where some Kipk students act as incapable individuals on the front stage but live hedonistic lives on the back stage. Ironically, modernization intended to make scholarship registration easier actually carries the risk of manipulation and hedonistic behavior among students.